Prioritizing Ecotourism Strategies Intagrated with Multiple-criteria Decision Analysis and SWOT Analysis: Masuleh-Iran Sample - Tajer, Elnaz; Demir, Sara (Bursa Uludağ Üniversitesi, 2022)
Ecotourism, unlike mass tourism, is a sustainable alternative tourism that can protect natural and cultural landscape values and historical sources of sensitive landscapes and ensures its ecological integrity. Ecotourism, which takes into account the balance of conservation and use, supports the sustainable use of resources. In this context, raising awareness of visitors and local people may lead to a decrease in urban pressure, visitor impact and environmental problems on natural and cultural landscape values that provide resources to ecotourism. Within the scope of this research, Masuleh village, which is close to the Hazar Sea, surrounded by Alborz mountains and forests, has cultural and historical heritage value and preserves its local architectural structure, has been determined as the study area. These natural and cultural landscape values of Masuleh, which was included in the list of historical heritage by UNESCO in 2007, are under threat due to the confusion of authority in the management structure. The aim of this study is to determine the ecotourism criteria that have ecotourism resources for Masuleh and to determine the ecotourism strategies that ensure the sustainability of these sensitive landscape values. In this context, a field study and literature review was carried out, and a questionnaire integrating the Best-Worst Method (HCM), which is one of the multi-criteria decision-making methods, and SWOT (Strengths-Weaknesses-Opportunities-Threats) Analysis applied with local people and experts. As a result of the survey, the ecotourism criteria consisting of 4 main and 20 sub-ecotourism criteria were ranked according to their priorities. As a result, the criterion of opportunities criteria "inclusion in the UNESCO's Historical Heritage Site tentative list" was determined as an ecotourism strategy that should be evaluated as a priority. The methods and outputs of this study can set an example in determining the ecotourism strategies of similar study areas.

Ekoturizm, kitle turizminin aksine doğal ve kültürel peyzaj değerlerine ve tarihi kaynakların sahip olduğu hassas peyzajları koruyan ve ekolojik bütünlüğünü sağlayan bir sürdürülebilir alternatif bir turizmdir. Koruma ve kullanma dengesini dikkate alan ekoturizm kaynakların sürdürülebilir kullanımını desteklemektedir. Bu kapsamda ziyaretçilerin ve yerel halkın bilinçlenmesi ekoturizme kaynak değer sağlayan doğal ve kültürel peyzaj değerleri üzerindeki kentsel baskının, ziyaretçi etkisi ve çevresel problemlerin azalmasına yol açabilecektir. Bu araştırma kapsamında Hazar Denizi’ne yakın, Alborz dağları ile ormanlarla çevrili, kültürel ve tarihi miras değeri olan ve yerel mimari yapısını koruyan Masuleh köyü çalışma alanı olarak belirlenmiştir. 2007 yılında UNESCO tarafından tarihi miras listesine alınan Masuleh’in sahip olduğu bu doğal ve kültürel peyzaj değerleri yönetim yapısındaki yetki karmaşası nedeni ile tehdit altındadır. Bu çalışmanın amacı, Masuleh için ekoturizm kaynak değeri taşıyan ekoturizm kriterlerini tespit etmek ve bu hassas peyzaj değerlerinin sürdürebilirliğini sağlayan ekoturizm stratejilerini belirlemektir. Bu bağlamda arazi çalışması ve literatür çalışması gerçekleştirilmiş, çok kriterli karar verme yöntemlerinden biri olan En İyi-En Kötü Yöntemi (EİKY) ile GZFT (Güçlü Yönler-Zayıflıklar-Fırsatlar-Tehditler) Analizini entegre eden, yerel halk ve uzmanlar ile gerçekleşmiş bir anket çalışması düzenlenmiştir. Anket çalışması sonucunda 4 ana ve 20 alt ekoturizm kriterden oluşan ekoturizm kriterleri önceliklerine göre sıralanmış sonuç olarak ”UNESCO’ nun Tarihi Miras Alanı geçici listesinde yer alması” kriteri, fırsat olarak öncelikli olarak değerlendirilmesi gereken bir ekoturizm stratejisi olarak belirlenmiştir. Bu çalışmanın yöntem ve çıktıları benzeri çalışma alanlarının ekoturizm stratejilerinin belirlenmesinde örnek model oluşturabilir.
Çok Kriterli Karar Verme Analizi ve GZFT Analizi Entegrasyonu ile Ekoturizm Stratejilerinin Önceliklendirilmesi: Masuleh-İran Çalışması
Keywords: Agricultural Engineering (Other); Ziraat Mühendisliği (Diğer)